Sicilian Domed Churches of the 11th–12th Centuries. The Architecture of Valdemone - Ismailova, Olga (Actual Problems of Theory and History of Art, 2017)
The study is dedicated to the development of domed buildings in Sicily. This subject has beenpoorly studied until recently. It has a number of prospects: the study of prominent features of Romanesque architecture, the Islamic and Byzantine influences on the architecture of the island, and the interplay with theculture of southern Italy — in the first instance, Calabria. Norman Sicily is often believed to be a separate region with its own architectural style. Nevertheless, in Sicily, there were a considerable number of schools, which were beyond the understanding of the Norman style. Except Palermo and the cities directly related to the court, there were areas where different architectural schools evolved. Such areas were Valdemone and Trapani surroundings.These centers have been studied to varying degrees.The study is concentrated on the architecture of Valdemone (Mili S. Pietro (Messina); S. Maria, Itala (Messina);S. Pietro (1092–1093); Casalvecchio (Vallata d’Agrò) Messina, SS. Pietro e Paolo (between 1116 and 1172)),where during the Islamic rule there were several centers with a Byzantine population. Formal independence from the Emirate of Sicily and a formal link with the court of Constantinople contributed not so much to the preservation of the Byzantine tradition, as to the close interaction of different cultures. We discuss some extant monuments that make a regional stylistic group and analyze them in conjunction with buildings in Calabria, southern Italy Norman monuments. Special attention has been devoted to the place and importance of the dome in the composition of the churches’ ensemble.
Keywords: architecture; medieval architecture of Sicily; Norman Sicily; domed churches